Telemedicine in the Health Communication Industry: A Systematic Review and Implications for Indonesia - Wardhani, Andanareswari; Permanasari, Febrina Galuh; Letare, Yolanda Natasia; Ernungtyas, Niken Febrina (Pelopor Publikasi Akademika, 2025)
Technological advancements have significantly transformed the healthcare sector, with telemedicine emerging as a key innovation that integrates healthcare services with the communication industry. Telemedicine, defined as the use of electronic communication to deliver healthcare remotely, offers notable benefits such as expanded access to services, cost efficiency, and enhanced quality of care. These advantages are particularly relevant in Indonesia, where geographical challenges and uneven population distribution often limit healthcare accessibility. The COVID-19 pandemic further accelerated telemedicine adoption globally and nationally, underscoring its critical role in ensuring service continuity during health crises. This study aims to analyze the development, challenges, opportunities, and future trends of telemedicine in relation to the communication industry. Employing a systematic literature review method, the research synthesizes findings from English-language journal articles indexed in Scopus to provide an evidence-based overview of telemedicine’s trajectory. The findings reveal that while telemedicine has improved access and efficiency, its implementation in Indonesia still faces barriers such as digital infrastructure limitations, regulatory gaps, and digital literacy disparities. Opportunities exist in strengthening policy frameworks, expanding broadband access, and fostering cross-sector collaborations between healthcare and communication industries. The study contributes to both healthcare and communication fields by highlighting telemedicine as a convergence point that requires integrated governance and innovation. The implications suggest that sustainable telemedicine development will depend on addressing structural barriers while leveraging technological growth to enhance equitable healthcare delivery in Indonesia.